Survey of interception in Sandridge woods - Bolla, Bence (JOURNAL OF LANDSCAPE ECOLOGY, 2015)
Interception (leafage interception, litter interception and discharge of trunks) is one the most important features of water-balance in forest stands. Water-balance is controlled by leafage interception entails a certain amount of precipitation held by the leafage that can either transpire or be absorbed by the leaves. Each specific type of forest has an impact on the quantity of interception. The survey completed in this study was conducted to determine the leafage interception of two neighboring woods. The research took place from the 15th of March, 2013 to the 4th of August, 2014 in Bócsa, Hungary. The forests were two monocultures planted using the same technology: a pine stand and a grey poplar stand. The control area was on open area next to the forests. Data was collected in the grey poplar forest only during the growing season, and in the pine forest throughout the year. Open surface precipitation was observed with a Hellmann rain gauge and a weather station in the control area. The proportion of discharge on the trunks and the foliage interception was determined with three Hellmann rain gauge units (one placed in a single tree row, another between two rows of trees, and the third was put in a thin grove) in both forests. Additionally, twenty funnels (each 280 cm2) applied meter wise and twenty rain gauge units (each 100 cm2) and sixty trunk collars were placed at random. The distribution and location of the rain gauge units and trunk collars were determined by the distribution of the height and diameter (at 1.3 m) of the trees and structure of the forest stands (quality, structure of branches, shape and density of leafage). The survey results showed that in the pine forest interception was 23 % and the amount of trunk discharge was 6 %, and within the grey poplar forest, the rate of interception was 19 % and trunk discharge was 15 % (concerning an area of 75x55 m).
Keywords: interception; water-balance; forest stands; Sandridge; Babócsa